Wanted dead or alive (probably dead): Stem group Polytrichaceae. Issue 8 (12th June 2018) - Bippus, Alexander C.; Escapa, Ignacio E.; Tomescu, Alexandru M. F.
Abstract : Premise of the Study: The Polytrichaceae are a widespread and morphologically isolated moss lineage. Early attempts to characterize phylogenetic relationships within the family suggested that morphology is not phylogenetically informative. Two well‐characterized fossils similar to basal and derived Polytrichaceae ( Meantoinea alophosioides and Eopolytrichum antiquum, respectively), are known from Cretaceous rocks. To assess the phylogenetic positions of these fossils and compare hypotheses of relationships recovered using molecular vs. morphological methods, we conducted a comprehensive morphology‐based phylogenetic study of Polytrichaceae. Methods: We evaluated the phylogenetic relationships of Polytrichaceae using a data set of 100 morphological characters (including 11 continuously varying traits codified as continuous characters) scored for 44 species of acrocarpous mosses and parsimony as the optimality criterion. Key Results: Continuous characters significantly increased the resolving power of the analyses. The overall ingroup topology was sensitive to rooting as determined by outgroup selection, with some analyses yielding results that were incongruent with those of molecular studies. Both fossils had stable phylogenetic relationships, irrespective of outgroup sampling. Conclusions: Our results suggest that morphology is useful in resolving phylogenetic relationships in the Polytrichaceae, if both discrete and continuous characters are used. However, our rooting experiments demonstrate that there is no superior way to root analyses and indicate that relationships within the family are best evaluated using unrooted networks without outgroup taxa. These rooting problems suggest that additional information is needed to understand the phylogenetic relationships of Polytrichaceae. Such additional information could come from fossils of stem group polytrichaceous mosses, which await discovery.